In vitro Shoot Regeneration in Elephant Foot Yam, Amorphophallus campanulatus Blume - Paul, K.K.; Bari, M.A.; Islam, S.M.S; Debnath, S.C. (Plant Tissue Culture and Biotechnology, 2013)
Plant Tissue Cult. & Biotech. 23(1): 121?126, 2013 (June) DOI: http://dx.doi.org/10.3329/ptcb.v23i1.15569